A PROTOTYPE OF LOW POWER ZIGBEE-GSM BASED AUTOMATIC METER READING SYSTEM - PRIMICANTA, RYO HANDOKO (2013)
Undoubtedly, conventional meter reading technique done by utility companies by sending their meter officers to the customer premises has arisesmany problems. From resource being used to do the task, time needed to complete the job until complains posted by unsatisfied customers because of meter reading inaccuration. This has been a serious problem faced by Tenaga Nasional Berhad (TNB) as a Malaysian utility company.